Partners of the empire - Yaycioglu, Ali (Stanford University Press, 2016)
Empire : order, crisis, and reform (1700-1806) – The notables : governance, power, and wealth – Communities : collective action, leadership, and politics – Crisis : riots, conspiracies, and revolutions (1806-1808) – Settlement : the Deed of Alliance and the empire of trust (1808)
Literaturangaben
Keywords: Political participation; Political culture